Properties of sandcrete blocks stabilized with cashew apple ash as a partial replacement for cement - Peter Korankye; Humphrey Danso (Scientific Reports, 2024)
Abstract The use of by-products from agricultural production as stabilizers in concrete and mortar in developing countries could result in numerous benefits. These by-products are readily available, cheap, and have a lesser carbon footprint. As Portland cement prices keep rising, the search for alternatives to sustainable construction materials is necessary. Cashew apples are left on cashew farms as waste material after the nuts have been removed due to lack of utilization. In this study, the properties of sandcrete blocks produced with cashew apple ash (CAA) as a partial replacement for cement were investigated. A total of 180 block specimens of size 100 × 100 × 130 mm were prepared from six different mortar mixes of control, 5, 10, 15, 20, and 25% CAA replacement of cement by weight were prepared. Results revealed that the highest compressive and tensile strengths after 28 days of curing CAA blocks were 11.45 and 1.08 N/mm2 respectively. The best water absorption resistance obtained was 2.66%. The study recommends the use of 5% CAA replacement of cement to block manufacturers for use in manufacturing sandcrete blocks. This study is useful because the cashew apple waste ash used as an alternative material to cement in sandcrete block production will be beneficial to the environment and may also save the cost of production of sandcrete blocks.